Gabapentinoids for treatment of neuropathic pain: a medicines usage evaluation at the Groote Schuur hospital chronic pain management clinic - Moabelo, Machuene (Department of Anaesthesia and Perioperative Medicine, 2021)
Background Neuropathic pain (NP), defined as pain caused by a lesion or disease of the somatosensory system, affects 6.9 – 10 % of people worldwide. Pregabalin is currently recommended as a first line drug for NP in South Africa. Methods A cross-sectional retrospective descriptive medicines usage evaluation (MUE) of Pregabalin at Groote Schuur Chronic Pain clinic for the year 2017 was conducted. A MUE using a standardized data collection form was performed on 100 randomly selected folders. Data are summarized using descriptive statistics. Results The majority of cases were women (76) with a mean age of 55.9y (SD12.49). A diagnosis of NP was recorded in 58 folders and a “possible” diagnosis recorded in 7 folders. In 79 cases there was no mention of a tool/method used to diagnose NP. The most common condition diagnosed was chronic post-surgical pain with a neuropathic component (n=16), followed by NP (n=15). The most common initiating and current dose of Pregabalin was 75mg twice daily. In 56 patients, Pregabalin was prescribed in conjunction with a tricyclic antidepressant (TCA) or selective noradrenaline reuptake inhibitor (SNRI). Patient education was documented as having taken place in 76 of cases. Conclusions Based on this MUE we recommend the use of screening tools for the diagnosis of neuropathic pain, and a focus on the initiating dose of Pregabalin. The use of a standardized assessment document and the interdisciplinary team input at this clinic appears to optimize prescribing of Pregabalin in line with practice guidelines.